Kandungan Informasi Pemberian Penghargaan Laporan Tahunan sebagai Indikasi Kepercayaan Masyarakat pada Konsep Corporate Governance - Wuryani, Eni (Akutansi Bisnis & Manajemen ( ABM ), 2007)
Corporate government is a concept that base on how importance accurate, up date and right on time information for stakeholder, also corporate duty for disclosure with accurate, right on time and transparent about corporate performance, ownership, and stake holder. Moreover Corporate Government principles hopefully can make financial report more quality so at the it can make increase user trusty of it and also for investor. This is a quantitative research using event study approach to see average abnormal return and positive stoke average trading volume activity and significant after annual report award. The result of T test show up that average abnormal return tear 2002 for all samples are positives abnormal return four days. Positive T but not significant happen in days (t-2), (t-0), (t+2), and (t+5). In comparison hypothesis using T Test in average trading volume activity years 2002 for all trade volume samples five days after announcement of annual report award not different with five days after annual report awards. Furthermore according to the result of average abnormal return years 2002 and average trading volume activity year 2002 show that market not interested with information of annual report award. It was indicated that public trust of corporate government is low. Significant T positive in average abnormal return 0.00661, it happen in days one after annual report award with alpha 10%.